Extreme overvalued beliefs and identities: revisiting the drivers of violent extremism - Kristinsdottir, Kolbrun; Ebner, Julia; Whitehouse, Harvey (Frontiers in Psychology, 2025)
Recent efforts to understand violent extremism have appealed to the concept of extreme overvalued beliefs as a way of explaining fixation and extremist commitments. Extreme overvalued beliefs refer to an ego-syntonic fixation that grows more intense, absolute and emotional over time and is shared with a sub-community. However, while extreme overvalued beliefs precede many targeted attacks, most people who hold them do not resort to violence. Previous research has highlighted four ‘ingredients’ associated with an increased risk of violent extremism, only three of which are captured in studies linking extreme overvalued beliefs to violence: perceived outgroup threat, demonization of the outgroup, and endorsement of violence. We argue that the fourth element—missing from the literature on extreme overvalued beliefs—is identity fusion: a visceral sense of oneness with the group in which personal and group identities become functionally equivalent. The goal of this paper is to improve current understanding of the circumstances where individuals with extreme overvalued beliefs turn into potential attackers. We show that when certain types of extreme overvalued beliefs are combined with identity fusion it can lead to violent self-sacrifice. Drawing on evidence from psychiatry, evolutionary anthropology, behavioural psychology and computational linguistics, along with a forensic analysis of three high-profile case studies of lone-actor grievance-fuelled violence, we explore the interplay of these risk factors and propose a more encompassing construct for explaining violent extremism. We call this hybrid framework Extreme Overvalued Beliefs and Identities (EOBI), synthesising the findings of interdisciplinary research on pathological fixation and identity fusion.